Hubungan Interaksi Sosial Guru Pendamping Dengan Empati Anak Autis di SLB Thiafin Mandiri Prabumulih - Adellia Agustrie; Neni Noviza; Bela Janare Putra (Social Science and Contemporary Issues Journal, 2024)
This research entitled “The Relationship between Social Interaction of Assistant Teachers anda Empathy of Autistic Children at SLB Thiafin Mandiri Prabumulih. This research aims to find out the relationship between the interaction of accompanying social teachers and the emphaty of autistic children at SLB Thiafin Mandiri Prabumulih. The method used is a quantitative approach with a correlational research type. The research population consistedof 15 people. The samplingtechniques uses a saturated sampling techniques because the populations < 100, so the population is included in the sample. The results of the validity test by comparing rcount with rtable from the formula df = n-2, namely 0,3610. The data analysis technique uses the Pearson product moment correlation test. The results of the research show that the average interaction of accompanying social teachers at SLB Thiafin Mandiri Prabumulih is at a medium level with a percentage of 73 % anda the emphaty level for the majority of autistic children is in the medium category with a percentage of 87 %. The results of the analysis using the Pearson product moment corrleation test obtained a value of 0,054 and the resultswere compared with the rtabel of the 15 people in the research sample which wasa 0,5140. So, the conclusion states that there is a positive relationship between the social interaction of accompanying teachers anda emphaty of autistic children at SLB Thiafin Mandiri.